PEMBERIAN REMISI BAGI PELAKU TINDAK PIDANA KORUPSI - Alfiana Dwi Putri Maesty; Hari Soeskandi (Gapenas Publisher, 2022)
The Corruption Eradication Law specifically regulates its own procedural law for law enforcement perpetrators of criminal cts of corruption. Broadly, the handling of corruption is distinguished from the handling of other special crimes. This type of research is normative legal research, namely research conducted by reviewing legal materials obtained through library research. In normative research, the written law is studied from several spects such s philosophical theory, comparison, structure or composition, consistency, general explanation nd explanation of each rticle, formality, nd binding power of law nd the language used is legal language. In the end, the criminal verdicts handed down by judges on corruption convicts will not be right on target, because the deterrent effect that was intended to be given to the corruption convicts to carry out self-improvement has not been chieved, because the convict can continue to experience reduction in his prison term nd the purpose of the sentence is not chieved. This lso pplies to prospective corruptors who see that remission will be tool to get out of prison easily so that the element of punishment, which is useful for scaring someone from committing crime will be reduced nd in the end it is feared that the increase in corruption will be difficult to contain. . In ddition, the Indonesian Correctional System ctually means fostering prisoners who have integrity with the community nd lead to the integrity of life nd livelihood. Correctional s process of moving by stimulating the emergence nd development of self-propelling djustment towards personal development through its own ssociations djusting to the integrity of life nd livelihood. Reducing the period of detention which will reduce the effect lso reduces the important essence of the penitentiary system, namely the period of detention is period of development, given the characteristics of this extraordinary crime of corruption